Morphoanatomic Analysis of Pollen at Marine Science Techno Park Jepara - Ahmad Syukron; Faat Nasyiruddin (Sekolah Tinggi Agama Islam Kuningan, 2025)
This study examines the influence of e-learning platform utilization on student learning engagement in secondary schools using a quantitative approach. The background of this study is the rapid adoption of educational technology post-pandemic, which demands a deeper understanding of how digital platforms influence student engagement in the formal learning process. The study population consisted of secondary school students in several public and private schools, with the sample obtained through a stratified random sampling technique to ensure representation based on grade level and school type. Data were collected using a standardized questionnaire that measured dimensions of e-learning utilization (accessibility, frequency of use, interactive features, and content quality) and dimensions of learning engagement (behavioral engagement, emotional engagement, and cognitive engagement). Validity and reliability tests of the instruments were conducted prior to analysis. Analytical techniques included descriptive statistics, Pearson correlation, and multiple linear regression to examine the magnitude and direction of the influence of e-learning utilization variables on learning engagement. The results showed that e-learning platform utilization was positively and significantly related to the level of student learning engagement; interactive features and content quality contributed the most to the variation in engagement. The practical implications of these findings include recommendations for platform developers, educators, and policymakers to optimize the design and integration of e-learning into curricula to enhance engagement and learning outcomes. This study also addresses methodological limitations and offers directions for further research examining long-term effects and the mediating role of factors such as self-efficacy and teacher support.